Chemical characteristics and fractionation of proteins from Moringa oleifera Lam. leaves - Borges Teixeira, Estelamar Maria [UNESP]; Barbieri Carvalho, Maria Regina [UNESP]; Neves, Valdir Augusto [UNESP]; Silva, Maraiza Apareci [UNESP]; Arantes-Pereira, Lucas (Elsevier B.V., 2014)
Moringa oleifera Lam, is a leguminous plant, originally from Asia, which is cultivated in Brazil because of its low production cost. Although some people have used this plant as food, there is little information about its chemical and nutritional characteristics. The objective of this study was to characterise the leaves of M. oleifera in terms of their chemical composition, protein fractions obtained by solubility in different systems and also to assess their nutritional quality and presence of bioactive substances. The whole leaf flour contained 28.7% crude protein, 7.1% fat, 10.9% ashes, 44.4% carbohydrate and 3.0 mg 100 g(-1) calcium and 103.1 mg 100 g(-1) iron. The protein profile revealed levels of 3.1% albumin, 0.3% globulins, 2.2% prolamin, 3.5% glutelin and 70.1% insoluble proteins. The hydrolysis of the protein from leaf flour employing sodium dodecyl sulfate (SDS) and 2-mercaptoethanol (ME) resulted in 39.5% and 29.5%, respectively. The total protein showed low in vitro digestibility (31.8%). The antinutritional substances tested were tannins (20.7 mg g(-1)), trypsin inhibitor (1.45 TIU mg g(-1)), nitrate (17 mg g(-1)) and oxalic acid (10.5 mg g(-1)), besides the absence of cyanogenic compounds. beta-Carotene and lutein stood out as major carotenoids, with concentrations of 161.0 and 47.0 mu g g(-1) leaf, respectively. Although M. oleifera leaves contain considerable amount of crude protein, this is mostly insoluble and has low in vitro digestibility, even after heat treatment and chemical attack. In vivo studies are needed to better assess the use of this leaf as a protein source in human feed. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Mineral; In vitro digestibility; Carotenoids; Antinutritional substances